Antara Hukum Murtad dalam Islam dengan Kebebasan Beragama dalam Hak Asasi Manusia (HAM) - Syamsuddin Syamsuddin (El-Mashlahah, 2021)
This article describes the law of apostasy in Muslim scholars' ijtihad and freedom of religion in terms of human rights. This research uses normative legal research methods. The research aims to describe and clarify the views of ulama on the law of apostasy and to dialogue with religious freedom as regulated in human rights. This research concludes that the majority of scholars consider apostasy as a criminal offense which is punishable by absolute death after refusing to revert to Islam. Few modernist liberals think that the death penalty is imposed only when there is hostility or rebellion committed when leaving Islam. As for universal human rights, it recognizes freedom of religion as well as freedom to change religions. This freedom is limited only to the freedoms of other people and other general freedoms. Religious freedom in Indonesia applies in a limited way by providing guarantees to embrace a religion, limiting freedom of religion in recognized religions, and protecting religion from blasphemy. Islam frees anyone to embrace a certain religion, but those who have chosen Islam are bound by the core values of hifz al-din (maintaining religion) so that apostasy is a criminal act.Keywords: Apostasy, freedom of religion, maintaining religion (hifz al-din), and human rights.Jurnal ini menjabarkan tentang hukum perbuatan murtad dalam ijtihad ulama dan kebebasan beragama dalam tinjauan hak asasi manusia. Penelitian menggunakan metode penelitian hukum normatif. Penelitian bertujuan untuk mendeskripsikan dan mentarjih pandangan ulama tentang hukum murtad serta medialogkan dengan kebebasan beragama yang diatur dalam Hak Asasi Manusia. Penelitian menyimpulkan bahwa mayoritas ulama menilai murtad termasuk tindak pidana yang dijatuhi hukuman mati secara mutlak setelah menolak masuk Islam kembali. Sebagian kecil (liberal modernis) menilai hukuman mati dijatuhkan hanya bila ada permusuhan atau pemberontakan yang dilakukan saat keluar dari Islam. Adapun hak asasi manusia universal mengenal kebebasan beragama sekaligus kebebasan berpindah agama. Kebebasan ini hanya dibatasi kebebasan orang lain dan kebebasan umum lainnya. Kebebasan beragama di Indonesia berlaku secara terbatas dengan memberikan jaminan memeluk agama, membatasi kebebasan beragama pada agama yang diakui, dan melindungi agama dari penistaan. Islam membebaskan siapapun untuk memeluk agama tertentu, namun bagi yang telah memilih Islam terikat dengan nilai pokok hifz al-din (menjaga agama) sehingga murtad termasuk perbuatan pidana.Kata Kunci: Murtad, kebebasan beragama, menjaga agama (hifz al-di>n), dan hak asasi manusia.